2014
DOI: 10.1136/bjsports-2014-093613
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviour and the risk of depression: a meta-analysis

Abstract: This meta-analysis of observational studies indicates that sedentary behaviour is associated with increased risk of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
265
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(291 citation statements)
references
References 47 publications
10
265
1
3
Order By: Relevance
“…Teychenne et al (2010b) reported that time spent in sedentary behavior was positively associated with onset of depression after adjusting for physical activity. Another meta-analysis reported similar findings on the independent effects of sedentary time and physical activity on mental health (Zhai et al 2015). Therefore, sedentary behavior is now con sidered to be a distinct domain of behavior that may pose a risk to health in its own right.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Teychenne et al (2010b) reported that time spent in sedentary behavior was positively associated with onset of depression after adjusting for physical activity. Another meta-analysis reported similar findings on the independent effects of sedentary time and physical activity on mental health (Zhai et al 2015). Therefore, sedentary behavior is now con sidered to be a distinct domain of behavior that may pose a risk to health in its own right.…”
Section: Introductionmentioning
confidence: 71%
“…First, many studies have reported that sedentary time was associated with cardiometabolic risk factors (Cappuccio et al 2011;Zhai et al 2015). In addition, colonic disease was associated with poor mental health (Cole and Dendukuri 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing interest in the association between sedentary behavior and mental health, and a recent meta-analysis demonstrated increased risk of depressive symptoms in adults reporting greater amounts of sedentary time (Zhai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since the area of sedentary behavior research has focused largely on negative aspects of mental function, such as depressive symptoms (Zhai et al, 2015), we also aimed to examine positive mental wellbeing. Indeed, wellbeing is not simply the absence of negative states but also the presence of positive affective states.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sedentary behavior is associated with a 112% increase in the relative risk (RR) for diabetes (RR 2.12; credible interval [CrI]=1.61-2.78), a 147% increase in the RR for cardiovascular events (RR 2.47; 95%CrI=1.44-4.24), a 90% increase in the risk of cardiovascular mortality (Hazard ratio, HR=1.90; 95%CrI=1.36-2.66) and a 49% increase in the risk of all-cause mortality (HR=1.49; 95%CrI=1.14-2.03) (Wilmot et al, 2012 (Zhai, Zhang, & Zhang, 2014). To date, subjective data and objective assessments of both total sedentary time (accelerometers) as well as the specific behavior of sitting (inclinometers) are missing in people with BED.…”
Section: How Can We Prevent Sedentary Behavior In People With Binge Ementioning
confidence: 99%